Persistent or permanent atrial fibrillation is associated with severe cardioembolic stroke in patients with non-valvular atrial fibrillation - Joji Hagii (Thrombosis Journal, 2021)
Abstract Background Little is known about the difference in the severity of cardioembolic (CE) stroke between patients with paroxysmal atrial fibrillation (PAF) and persistent/permanent AF (PerAF). We assessed stroke severity in patients with CE stroke divided by the type of AF. Methods Three hundred and fifty-eight consecutive patients with CE stroke within 48 h of onset and with a modified Rankin Scale (mRS) score ≤ 1 before onset were studied. We compared basic characteristics, stroke severity, and functional outcome between patients with PAF (n = 127) and PerAF (n = 231). Results Patients with PerAF were more likely to take oral anticoagulants (OACs) than those with PAF (37% vs. 13%, P <  0.0001), even though still underuse of OAC in both patients. Regarding stroke severity on admission, patients with PerAF exhibited a tendency toward a higher score on the National Institutes of Health Stroke Scale (NIHSS) compared with patients with PAF (12 [5–20] vs. 9 [4–18]; P = 0.12). Mortality and mRS score at discharge were higher in the PerAF than in the PAF group (13% vs. 4%; P = 0.005, and 3 [1–5] vs. 2 [1–4]; P = 0.01, respectively). Multivariate analyses confirmed that PerAF was a significant determinant of severe stroke (NIHSS score > 8) on admission (odds ratio [OR] to PAF = 1.80; 95% confidence interval [CI] 1.08–2.98; P = 0.02) and of an mRS score ≥ 3 at discharge (OR = 2.07; 95% CI 1.24–3.46; P = 0.006). Patients with PerAF had three times more internal carotid artery occlusion evaluated by magnetic resonance angiography, which indicated a more severe cerebral embolism compared with patients with PAF. Conclusions We found underuse of OAC in high risk AF patients with CE stroke. PerAF is significantly associated with severe stroke on admission and an unfavorable functional outcome at discharge in Japanese patients with CE stroke.